Synthesis of superabsorbent carbonaceous fibre polymer via inverse-suspension polymerization for NPK coating - Munirah Ezzah, Tuan Zakaria (2019)
Recently, the use of controlled-release fertiliser (CRFs) in agriculture has resulted in huge benefits in plant growth and cultivation. CRF is a type of modified fertiliser where a conventional fertiliser is conjoining with various materials, mostly polymers, creating a fertiliser with the ability to release nutrients in controlled manner. A superabsorbent polymer-coated fertiliser has the advantage in retaining water in soil after irrigation and also releasing nutrients into the soil slowly and under control. This study aimed to produce a nitrogen-phosphorus-potassium (NPK) fertiliser coated with superabsorbent carbonaceous fibre polymer (SPC) that possesses water-retention and controlled-release properties. In order to achieve the main objective, this study was divided into three different stages: producing carbonaceous fibre from natural kenaf fibre through a hydrothermal carbonisation (HTC) process; synthesising superabsorbent polymer (SAP) and superabsorbent carbonaceous fibre polymer (SPC) via inverse-suspension polymerisation; and lastly, producing and investigating the controlled-release and water-retention properties of NPK coated with SAP/SPC (the CRF). Firstly, the production of carbonaceous fibre from kenaf through HTC over different operating times was examined. An elemental analyser was used to measure the carbon content after HTC and indicated that carbon yield increases with time, with 12 h as the optimal operating time to produce the highest yield: 64.47%. Characterisation of the carbonaceous fibre was made with FTIR and SEM. Then, the SPC polymers with different amounts of filler (0.01, 0.02, 0.03, 0.04 and 0.05 wt %) were synthesised with SAP as control. The water absorbency ability of SAP and SPC were investigated using the tea bag method. SPC samples with 0.04 wt % had the optimal water absorbency ability (55.279 g water/g sample). Characterisation of SAP and SPC were observed through FTIR, FESEM and EDX analyses. Later, NPK fertilisers coated with SAP or SPC were produced and investigation of water retention in soil was made for 30 days, varying two different parameters: different coating material and different weight percentage of NPK coated with SPC. NPK coated with SAP or SPC proved to have high water-retention ability in soil compared to uncoated NPK. NPK coated with SPC showed better results than NPK coated with SAP, with more than 80% water retained after 30 days of experiment. In addition, the higher the weight percentage of NPK coated with SPC in the soil, the greater its water retention. The slow-release behaviour of all of the CRF samples were observed using ICP-MS spectrometry. Over 30 days, all samples of NPK coated with SAP/SPC had low release rates, with less than 50% nutrient release compared to uncoated NPK. NPK coated with SPC showed the lowest release rate. The release mechanism kinetics of NPK coated with SAP/SPC approached Fickian diffusion-controlled release as the n value for both samples were less than 0.5. In conclusion, Carbonaceous fibre from Kenaf was successfully incorporated into the SPC, improving the polymer performance in terms of water absorbency, water retention in soil and its controlled release mechanisms.